2021
DOI: 10.21203/rs.3.rs-310839/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Climate drives long-term change in Antarctic Silverfish along the western Antarctic Peninsula

Abstract: Over the last half of the 20th century, the western Antarctic Peninsula has been one of the most rapidly warming regions on Earth, leading to substantial reductions in regional sea ice coverage. These changes are modulated by atmospheric forcing, including the Amundsen Sea Low (ASL) pressure system. We utilized a novel 25-year (1993–2017) time series to model the effects of environmental variability on larvae of a keystone species, the Antarctic Silverfish (Pleuragramma antarctica). Antarctic Silverfish use se… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 41 publications
0
1
0
Order By: Relevance
“…As P. antarcticum requires platelet ice for early life stages (eggs and larvae; Guglielmo et al, 1998;Vacchi et al, 2004Vacchi et al, , 2012Ghigliotti et al, 2017), reduction in this ice type leads to poor recruitment of the fish. Evidence from the Antarctic Peninsula (La Mesa et al, 2015;Corso et al, 2022) has shown that numbers of P. antarcticum have decreased substantially in line with reductions in sea ice. Consequent effects include increases in copepods and krill and their predators, myctophid fish, while salps decrease.…”
Section: Responses Of the Biological Systemmentioning
confidence: 99%
“…As P. antarcticum requires platelet ice for early life stages (eggs and larvae; Guglielmo et al, 1998;Vacchi et al, 2004Vacchi et al, , 2012Ghigliotti et al, 2017), reduction in this ice type leads to poor recruitment of the fish. Evidence from the Antarctic Peninsula (La Mesa et al, 2015;Corso et al, 2022) has shown that numbers of P. antarcticum have decreased substantially in line with reductions in sea ice. Consequent effects include increases in copepods and krill and their predators, myctophid fish, while salps decrease.…”
Section: Responses Of the Biological Systemmentioning
confidence: 99%